2011
DOI: 10.1097/cji.0b013e3182056ec4
|View full text |Cite
|
Sign up to set email alerts
|

Use of Curcumin to Decrease Nitric Oxide Production During the Induction of Antitumor Responses by IL-2

Abstract: Nitric oxide (NO) synthesis is strongly induced during interleukin (IL)-2 treatment of mice and humans. Although this free radical can act as a cytotoxic effector molecule against cancer cells, immunosuppressive effects have also been suggested. We evaluated the effects of curcumin on IL-2-induced NO synthesis and IL-2-induced antitumor responses in a mouse ascites tumor model. Curcumin inhibited inducible nitric oxide synthase (iNOS) expression and NO production, and thereby enhanced the proliferation and cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In recent years, curcumin and its derivatives have demonstrated promising anti-inflammatory activities by inhibiting several important inflammatory mediators such as tumor necrosis factor (TNF)-α, IL-6, IL-1β, nitric oxide (NO) and nitric oxide synthase (iNOS) [ 26 , 27 ]. The therapeutic potentials of curcumin are attributed mainly to its chemical structure, in which the presence of various substituents such as methoxy, hydroxyl, alkyl, halogens, amino, nitro, nitril, acetamido, carboxyl, benzene, heterocyclic and condensed rings in their structure may influence their specific biological activities to a certain degree [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, curcumin and its derivatives have demonstrated promising anti-inflammatory activities by inhibiting several important inflammatory mediators such as tumor necrosis factor (TNF)-α, IL-6, IL-1β, nitric oxide (NO) and nitric oxide synthase (iNOS) [ 26 , 27 ]. The therapeutic potentials of curcumin are attributed mainly to its chemical structure, in which the presence of various substituents such as methoxy, hydroxyl, alkyl, halogens, amino, nitro, nitril, acetamido, carboxyl, benzene, heterocyclic and condensed rings in their structure may influence their specific biological activities to a certain degree [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides COX-2, inducible nitric oxide synthase (iNOS) is also known to be implicated in inflammatory responses (63). Indeed, iNOS is reported to be another target for curcumin (64). iNOS results in NO generation, a wellknown pro-inflammatory mediator (65).…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…Many studies have reported inhibition of proliferation and induction of apoptosis in response to various anti-cancer reagents like NO-aspirin [42,43], quercetin [44][45][46], curcumin [47][48][49], and resveratrol [50,51]. Here, we report that compounds 1-3 induced colon cancer cell death via an anti-proliferative/proapoptotic mechanism.…”
Section: Uptake Of Compounds 1-3 Was Detected Via Flow Cytometrymentioning
confidence: 59%